SMARTPHONE MENJADI KEBUTUHAN PRIMER MAHASISWA DALAM AKTIVITAS PERKULIAHAN - Sheila Wijayanti (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2022)
Technology in communication has a role as academic support. It is due to the need to have knowledge and information from the right sources, which is prioritized. Technological developments have an impact on the existence of a relationship in communication between humans that allows each other to take place without being limited by distance, space, and time. Various communication functions have been incorporated into communication tools, namely Smartphones. Smartphones are Smartphones that have been developed with advanced technology in today's modern era. Its ability to innovate starting from features, usability and resolution is integrated into its operating system. The presence of this Smartphone provides many benefits and conveniences for consumers, especially students. The use of Smartphones also depends on the consumers who use them. Students find it helpful to have a Smartphone in finding information and increase knowledge, as well as supporting activities in lectures. The qualitative method is the method used in this study which requires interviews from respondents using a quota sampling technique as many as 35 people who are students of the History of Islamic Civilization Study Program at the Universitas Nahdlatul Ulama Indonesia. The variable is taken from the activities of students who often use their Smartphones in lecture activities, especially in class. The results of this study indicate that the respondents consider Smartphone is a primary need that must be owned in this modern era, without a Smartphone, students can think that they will be left behind with the various information needed.